Spatioselective Deposition of Passivating and Electrocatalytic Layers on Silicon Nanowire Arrays. - Wendisch, Fedja J.; Abazari, Mehri; Werner, Valerie; Barb, Horia; Rey, Marcel; Görlitzer, Eric; Vogel, Nicolas; Mahdavi, Hossein; Bourret, Gilles R. (ACS Applied Materials and Interfaces, 2020)
Metal–silicon nanowire array photoelectrodes provide a promising architecture for water-splitting because they can afford high catalyst loading and decouple charge separation from the light absorption process. To further improve and understand these hybrid nanowire photoelectrodes, control of the catalyst amount and location within the wire array is required. Such a level of control is currently synthetically challenging to achieve. Here, we report the synthesis of cm2-sized hybrid silicon nanowire arrays with electrocatalytically active Ni–Mo and Pt patches placed at defined vertical locations within the individual nanowires. Our method is based on a modified three-dimensional electrochemical axial lithography (3DEAL), which combines metal-assisted chemical etching (MACE) to produce Si nanowires with spatially defined SiO2 protection layers to selectively cover and uncover specific areas within the nanowire arrays. This spatioselective SiO2 passivation yields nanowire arrays with well-defined exposed Si surfaces, with feature sizes down to 100 nm in the axial direction. Subsequent electrodeposition directs the growth of the metal catalysts at the exposed silicon surfaces. As a proof of concept, we report photoelectrocatalytic activity of the deposited catalysts for the hydrogen evolution reaction on p-type Si nanowire photocathodes. This demonstrates the functionality of these hybrid metal/Si nanowire arrays patterned via 3DEAL, which paves the way for investigations of the influence of three-dimensional geometrical parameters on the conversion efficiency of nanostructured photoelectrodes interfaced with metal catalysts.
Keywords: Metals; Nanowires; Nanowire arrays; Catalysts; Deposition